2008
DOI: 10.4085/1062-6050-43.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Fatigue and Glenohumeral Kinematics in Participants Without Shoulder Dysfunction

Abstract: Context: Researchers have established that superior migration of the humeral head increases after fatigue of the rotator cuff muscles. In these studies, the investigators used imaging techniques to assess migration of the humeral head during statically held shoulder positions. Their results may not represent the amount of superior humeral head migration that occurs during dynamic arm elevation.Objective: To investigate the effect of rotator cuff fatigue on humeral head migration during dynamic concentric arm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 35 publications
4
72
0
1
Order By: Relevance
“…One study demonstrated monotonic superior translation of the humeral head, 33 2 other studies observed the humerus moving first superiorly and then inferiorly during arm elevation, 10,20 and 3 others observed the humerus being essentially fixed with respect to the glenoid during arm elevation. 5,7,12 The absence of glenohumeral translation is surprising and counterintuitive, as one would expect the deltoid to produce superior humeral translation in the early abduction arc-the so-called "setting phase"-before the rotator cuff muscles stabilize the joint.…”
Section: T T Resultsmentioning
confidence: 99%
“…One study demonstrated monotonic superior translation of the humeral head, 33 2 other studies observed the humerus moving first superiorly and then inferiorly during arm elevation, 10,20 and 3 others observed the humerus being essentially fixed with respect to the glenoid during arm elevation. 5,7,12 The absence of glenohumeral translation is surprising and counterintuitive, as one would expect the deltoid to produce superior humeral translation in the early abduction arc-the so-called "setting phase"-before the rotator cuff muscles stabilize the joint.…”
Section: T T Resultsmentioning
confidence: 99%
“…In the group after the exercise, the superior translation of the humeral head was discovered (2.8 mm) in shoulder abduction from 0° to 90°, and inferior translation was discovered (0.3 mm) from 90° to 135° [26]. A later study also found that the superior translation of the humeral head was discovered (average, 0.79 mm) in shoulder abduction after the fatigue of the supraspinatus, infraspinatus, and teres minor muscles [35].…”
Section: Discussionmentioning
confidence: 63%
“…Another study found that the superior translation of the humeral head increases regardless of the angle [35]. Both studies investigated healthy participants without any shoulder disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In overhead sports such as tennis, badminton, vol- from a joint position sense (JPS) perspective [1]. As 7 such it may be considered as an aetiological risk fac-8 susceptible to a reduction in performance or indeed an 10 increased occurrence of injury.…”
Section: Introductionmentioning
confidence: 99%